18F-FDG PET for Detection of Primary Tracheobronchial T-/Natural Killer–Cell–Derived Posttransplant Lymphoproliferative Disorder After Lung Transplantation. (December 2017) - Derlin, Thorsten; Braubach, Peter; Kreipe, Hans Heinrich; Hueper, Katja
Abstract : Abstract: Posttransplant lymphoproliferative disorder (PTLD) is a rare, but potentially devastating complication of solid organ transplantation. Epstein-Barr virus–associated PTLDs of T-cell origin are exceedingly rare. We present the case of a 20-year-old man with extranasal T-/natural killer–cell–derived PTLD after lung transplantation who underwent an 18 F-FDG PET/CT scan for staging of disease. The 18 F-FDG-PET scan demonstrated an unusual pattern of lymphomatous involvement limited to the recipients tracheobronchial tree without concomitant involvement of the donor's bronchi. This case highlights the potential of 18 F-FDG PET/CT for sensitive detection and staging of uncommon manifestations of PTLD.